2016
DOI: 10.1186/s11671-016-1546-y
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Tribological Performances of the SiO2/MoS2 Hybrid Nanofluids for Magnesium Alloy-Steel Contacts

Abstract: Hybrid nano-materials offer potential scope for an increasing numerous novel applications when engineered to deliver availably functional properties. In the present study, the SiO2/MoS2 hybrid nanoparticles with different mass ratios were employed as lubricant additives in the base oil, and their tribological properties were evaluated using a reciprocating ball-on-plate tribometer for magnesium alloy-steel contacts. The results demonstrate that the SiO2/MoS2 hybrid nanoparticles exhibit superior lubrication pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(30 citation statements)
references
References 44 publications
(48 reference statements)
0
29
0
1
Order By: Relevance
“…The formation of tribo-film can reduce the coefficient of friction (COF) since some nanoparticles tend to be adsorbed or embedded on surfaces. The nanoparticles can also mend surface defects to improve the load capacity by lowering the local stress concentration in order to protect the surfaces against further catastrophic damage [ Gara et al, 2013, Sahoo et al, 2013, Battez et al, 2008, Yu et al, 2008, Xie et al, 2016, Luo et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of tribo-film can reduce the coefficient of friction (COF) since some nanoparticles tend to be adsorbed or embedded on surfaces. The nanoparticles can also mend surface defects to improve the load capacity by lowering the local stress concentration in order to protect the surfaces against further catastrophic damage [ Gara et al, 2013, Sahoo et al, 2013, Battez et al, 2008, Yu et al, 2008, Xie et al, 2016, Luo et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research studies only considered the tribological characteristics of nanofluids on hard materials such as steel and cast iron [Gara et al, 2013, Sahoo et al, 2013, Battez et al, 2008, Xie et al, 2016. Few papers considered applications of nanofluids on relatively soft non-ferrous materials, such as copper, brass and aluminum.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al 5 studied the nanouid ow of Al 2 O 3 /water and Cu-Al 2 O 3 /water hybrid nanouids in the presence of a magnetic eld in the transverse direction through a porous channel where they set a comparison of the heat enhancement level due to the suspension of aluminum and copper nanoparticles in waterbased nanouids as both a unitary and a hybrid nanouid. Xie et al 6 examined the tribological characteristics of the SiO 2 / MoS 2 hybrid nanoparticles by studying the friction coefficient and wear volume. They concluded that the hybrid nanouids attain a lower wear volume and friction coefficient when compared to those of pure nanouids.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids containing molybdenum disulfide (MoS 2 ), graphite, tungsten disulfide (WS 2 ), and other nanoparticles with a lamellar structure have also exhibited lower friction compared to the base fluid. The lower friction is attributed to solid lubrication by lamellar-structed nanoparticles, which provide an easy shearing surface between contacting surfaces [13,[18][19][20]. Additionally, MoS 2 nanoparticles in nanofluids have been shown to form a tribofilm, resulting in lowering friction, and to deagglomerate wear particles for reduced transfer films [21,22].…”
Section: Introductionmentioning
confidence: 99%